x^2+y^2+13=6x-4y求x^y的值
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 19:31:06
x^2+y^2+13=6x-4y求x^y的值x^2+y^2+13=6x-4y求x^y的值x^2+y^2+13=6x-4y求x^y的值x^2+y^2+13=6x-4y求x^y的值x²-6x+9
x^2+y^2+13=6x-4y求x^y的值
x^2+y^2+13=6x-4y求x^y的值
x^2+y^2+13=6x-4y求x^y的值
x^2+y^2+13=6x-4y求x^y的值
x²-6x+9+y²+4y+4=0
(x-3)²+(y+2)²=0
∴x-3=0
y+2=0
∴x=3
y=-2
∴x^y=3^(-2)=1/9
已知x^2+y^2+13-4x+6y=0,求(2x-y)^2-2(2x-y)(x+2y)+(x+2y)^2
x^2+y^2+6x-4y+13=0求x,y,x^2-y^2的值
已知:x^2+y^2+4x-6y+13=0,求x^y值.
x^2+y^2+4x-6y+13=0,求x^y的值
x^2-4x+y^2-6y+13=0求x,y的值
若x^2+y^2-6x+4y+13=0 求x+y
x^2+y^2+13=6x-4y求x^y的值
x^2+y^2+13=6x-4y,求x^y的值
x^2+y^2+13=6x-4y求x^y的值
因式分解 若 x^2+4x+y^2-6y+13=0 求y^x
化简求值:已知x、y满足:x^2+y^2-4x+6y+13=0 求代数式 的值.(3x+y)^2-3(3x-y)(x+y)-(x-3y)(x+3y)急用!
已知x²+y²-6x+4y+13=0,求(2x-y)²-2(2x-y)(x+2y)+(x+2y)²已知x²+y²-6x+4y+13=0,求(2x-y)²-2(2x-y)(x+2y)+(x+2y)²
如果|X|=4 |Y|=2 且|X+Y|=X+Y 求X+Y
x,y 满足x(x-2)-y(y-6)=-10,求x,y的值
x-y/x-x+y/y-(x+y)(x-y)/y² y/x=2
已知x、y满足x2+y2-4x+6y+13=0 求代数式(3x+y)2-3(3x-y)(x+y)-(x-3y)(x+3y)已知x、y满足x^2+y^2-4x+6y+13=0 求代数式(3x+y)^2-3(3x-y)(x+y)-(x-3y)(x+3y)的值
2x-y=2,求[(x²+y²)-(x-y)²+2y(x-y)]÷4y
已知x*x-4xy+4y*y=0 求[2x(x+y)-y(x+y)]/(4x*x-4xy+y*y)的值?